DESIRING DOMINATION: A POSTFEMINIST STUDY ON THE LYRICS OF LANA DEL REY’S ULTRAVIOLENCE ALBUM - Galant Nanta Adhitya; Nadia Lasari (Universitas Gadjah Mada, 2019)
Feminist movements are said to have served their purposes and achieved equality, empowerment, and emancipation for women. America thus enters the era of postfeminism. A redefined image of independent and free-spirited yet feminine women is brought through popular cultural products, creating a shift in the view of 21st century American women, one of which can be seen from their response toward male domination. It is expressed in the lyrics of songs compiled in Lana Del Rey’s Ultraviolence album. This study employs descriptive qualitative method by treating the lyrics with the same approach as poetry. The data are in the form of language features, such as words, phrases, clauses, lines, and verses related to women’s response to male domination. McRobbie’s notion of double entanglement allows this study to borrow the feminist concept of male domination. There are five male dominating conducts found in the lyrics: 1) marginalization in “Sad Girl”; 2) subordination in “Shades of Cool”, 3) stereotype in “The Other Woman”; 4) physical and psychological violence in “Ultraviolence”, sexual violence in “Fucked My Way Up to the Top”; 5) domestic workload in “Old Money”. Meanwhile, the women’s response toward male domination is expressed in “Brooklyn Baby”. The progressive postfeminists approach male domination differently from the conservative feminists. The female speaker of the lyrics comprehend that her men’s conducts are dominating her, yet she receives them with a manner full of desire. For her, every relationship has the luxury to define their own rules as long as there is a consensual agreement from both parties involved.